2020
DOI: 10.1093/jee/toaa100
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Costs of Limb Regeneration and Their Transgenerational Consequences in Two Nearctic Lady Beetles (Coleoptera: Coccinellidae)

Abstract: We examined the ability of Coleomegilla maculata DeGeer and Hippodamia convergens Guerin-Meneville to regenerate, during pupation, a foreleg amputated in the fourth instar. Leg regeneration was complete for 80.7% of amputated H. convergens larvae, with 12.5% regenerating partially, and 6.8% showing no regeneration. Regeneration in C. maculata was 72.2% complete, 20.5% partial, and 7.2% none, but mortality following ablation was slightly higher than for H. convergens (7.4 vs. 0.6%). Ablation/regeneration caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…No significant difference was observed among the fresh BWs of amputated and unamputated adult beetles indicating the absence of tradeoff in BW with respect to regeneration. Similar results were found in other ladybird species: Hippodamia convergens Guérin‐Méneville and Coleomegilla maculata (DeGeer), where the regenerated adults showed no change in BW postemergence (Michaud, Abdelwahab, et al, 2020). Possibly, the beetle chose to compromise in the size of the regenerated appendage over BW.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…No significant difference was observed among the fresh BWs of amputated and unamputated adult beetles indicating the absence of tradeoff in BW with respect to regeneration. Similar results were found in other ladybird species: Hippodamia convergens Guérin‐Méneville and Coleomegilla maculata (DeGeer), where the regenerated adults showed no change in BW postemergence (Michaud, Abdelwahab, et al, 2020). Possibly, the beetle chose to compromise in the size of the regenerated appendage over BW.…”
Section: Discussionsupporting
confidence: 82%
“…Such reduction in the size of regenerated appendages has also been reported in mantids (Karuppanan, 1998), damselflies (Parvin & Cook, 1968), cockroaches (Tanaka et al, 1992), fishes (Mari‐Beffa et al, 1999), and amphibians and lizards (Fitch, 2003; Ritzman et al, 2012). While regeneration potential has clear advantages (Michaud, Abdelwahab, et al, 2020; Saxena et al, 2016; Wang et al, 2015), costs such as reduced limb size, delayed developmental duration (Saxena et al, 2016; Wu et al, 2019), reduced and disproportionate wings in stick insects (Maginnis, 2006b) have been reported. In previous studies on ladybird beetles, the ability to regenerate lost limbs is reported to be broadly conserved in 16 species including C. sexmaculata (Michaud, Nedved, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, autotomy is often assumed to yield long-term consequences on fitness, as detached appendages or body parts often play a role in courtship, mating, or sperm transfer (reviewed in Emberts et al 2019). Evidence regarding the effects of autotomy on reproduction is equivocal nonetheless, as the loss of body parts is known to bring negative, neutral, or even positive effects to reproduction (Emberts et al 2019;Michaud et al 2020;Cirino et al 2021;García-Hernández and Machado 2021;Talavera et al 2021). For example, after 'tail' autotomy, female scorpions experienced decreased fecundity, whereas males did not experience decreases in mating success (García-Hernández and Machado 2021).…”
Section: Introductionmentioning
confidence: 99%